Prevalence of Work-Related Neck and Shoulder Disorders with Associated Risk Factors and Disability among Primary School Teachers in Nilai, Negeri Sembilan, Malaysia - Kee, W.J.; S., Ambusuam; Labao, Hernan C.; Brown, J. (INTI International University, 2019)
Work-related neck and shoulder disorders (WRNSDs) have been reported among school teachers due to high demands of tasks involved with the job. This study aims to determine the prevalence of WRNSDs and its associated risk factors among primary school teachers in Nilai, Negeri Sembilan. A cross-sectional study was used to collect demographic and lifestyle factors using a validated self-administered questionnaire while the prevalence of neck and shoulder disorders were determined using Standard Nordic Questionnaire (SNQ) and Neck Disability Index (NDI) respectively. Moderate level of disability with high prevalence of neck pain (52.2%) and shoulder pain (39.1%) were reported in the past year. Age, years of experience, duration of working hours, and occupational factors show significant association to neck and shoulder pain. Results imply that WRNSDs are common among primary school teachers which are strongly associated with personal, task, and occupational factors. Education on posture and ergonomic features are recommended to address these problems and potentially improve their quality of life